2015
DOI: 10.1007/s00103-014-2105-2
|View full text |Cite
|
Sign up to set email alerts
|

Biometrische Entscheidungsunterstützung in Zulassung und Nutzenbewertung am Beispiel der Implikationen von heterogenen Ergebnissen in Untergruppen der Studienpopulation

Abstract: In the context of both drug licensing and reimbursement, the target population is sometimes restricted to a specific subgroup. In the setting of drug licensing the discussion concerns a negative benefit/risk assessment in a relevant subgroup. For reimbursement the debate involves the detection of an additional benefit compared with standard treatment, which can in some situations not be accepted for the overall study population. In their Methods Paper, the Institute for Quality and Efficiency in Health Care (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Conversely, clinical trials are generally not designed for detecting subgroup heterogeneity, so statistical tests may miss important interactions due to low power . This is particularly challenging as approaches need to account for both issues simultaneously, as illustrated by Gonnermann who also concluded that further work was needed to understand alternative statistical approaches in this area. Despite these issues, potential subgroup differences cannot be ignored, so it is still necessary to understand potential subgroup heterogeneity, and as such, consideration needs to be given for how such effects are to be analysed and interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, clinical trials are generally not designed for detecting subgroup heterogeneity, so statistical tests may miss important interactions due to low power . This is particularly challenging as approaches need to account for both issues simultaneously, as illustrated by Gonnermann who also concluded that further work was needed to understand alternative statistical approaches in this area. Despite these issues, potential subgroup differences cannot be ignored, so it is still necessary to understand potential subgroup heterogeneity, and as such, consideration needs to be given for how such effects are to be analysed and interpreted.…”
Section: Introductionmentioning
confidence: 99%